2009
DOI: 10.1243/09544119jeim515
|View full text |Cite
|
Sign up to set email alerts
|

The accuracy and precision of a micro computer tomography volumetric measurement technique for the analysis of in-vitro tested total disc replacements

Abstract: Total disc replacements (TDRs) in the spine have been clinically successful in the short term, but there are concerns over long-term failure due to wear, as seen in other joint replacements. Simulators have been used to investigate the wear of TDRs, but only gravimetric measurements have been used to assess material loss. Micro computer tomography (microCT) has been used for volumetric measurement of explanted components but has yet to be used for in-vitro studies with the wear typically less than < 20 mm3 per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 5 publications
1
11
0
Order By: Relevance
“…The fourteen discs were also scanned using a microCT scanner (Scanco µCT80, Scanco Medical, Busserdorf, Switzerland) using a resolution of 36µm with the use of a 1024 × 1024 plane image matrix, voltage of 70kVp and current of 114µA. The volume of each core was calculated using a segmentation method to separate polyethylene and air and then performing a simple voxel count [16]. …”
Section: Methodsmentioning
confidence: 99%
“…The fourteen discs were also scanned using a microCT scanner (Scanco µCT80, Scanco Medical, Busserdorf, Switzerland) using a resolution of 36µm with the use of a 1024 × 1024 plane image matrix, voltage of 70kVp and current of 114µA. The volume of each core was calculated using a segmentation method to separate polyethylene and air and then performing a simple voxel count [16]. …”
Section: Methodsmentioning
confidence: 99%
“…The intra-observer and inter-observer variability reported here compares well to other wear volume measurement techniques, which have been primarily applied to components from total hip replacement. Bowden et al [3] used micro-CT to measure the wear volume in retrieved acetabular liners. They reported intra-observer and interobserver variability of approximately 10%, with the variability increasing to 50% for one liner with a low volume of wear.…”
Section: Discussionmentioning
confidence: 99%
“…A number of in vitro laboratory tools have been developed to quantify the gravimetric or volumetric changes (due to wear) in polyethylene components that have been retrieved from patients or undergone wear simulator testing. Recently, micro-computed tomography (micro-CT) has been used to measure the overall volume of polyethylene tibial inserts, acetabular liners, and spinal discs [1][2][3], and to measure the volume loss due to wear in retrieved polyethylene acetabular liners [4]. Techniques have also been developed to measure and map the three-dimensional surface deviations due to wear in tibial inserts and acetabular liners [1][2].…”
Section: Introductionmentioning
confidence: 99%
“…Although micro-CT has been demonstrated to be accurate and highly repeatable for quantification of volumetric wear in retrieved polyethylene acetabular liners, scanner error up to 0.6% has been reported (Bowden et al, 2005). Vicars et al (2009) reported a volume measurement resolution of ±3 mm 3 for micro-CT of the polyethylene cores from total disc replacements, and recommended that gravimetric analysis should be used alongside micro-CT to ensure accuracy. We observed an excellent agreement between micro-CT and gravimetric volumes in this study, to a mean difference of 0.42%.…”
Section: Discussionmentioning
confidence: 99%
“…The liners were scanned with micro-computed tomography (micro-CT) and underwent 3D surface analysis using a previously described approach (Teeter et al, 2010;Vicars et al, 2009;Bowden et al, 2005). A new, never-implanted liner of the same type as the retrieved liner (Reflection, Smith and Nephew, Memphis, TN; 20 degree overhang, size H, 32 mm inner diameter, 62-64 outer diameter) was also scanned to serve as an unworn reference for the surface analysis.…”
Section: Micro-ct Scanning and 3d Surface Analysismentioning
confidence: 99%